IOT Based Smart Agriculture Monitoring System - Sweta Patel; Dr. Hiral Desai; Prof. Karuna Soni; Prof. Raju Swami (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
India is an agricultural country. Water is the most important resource of agriculture. currently farming accounts for 83% of India’s total water consumption. Using various smart farming tools, farmers are actively involved in livestock and crop cultivation. this page presents a concept based on the IoT smart farming system. Advanced technology is used on this home page Smart agriculture through IoT and automation. In this way, the water available for plants is monitored. With sensors, water is provided through irrigation if needed. This project is about how irrigation can be done. For efficient use with IoT. In this proposed method, we use different hardware such as ground sensors, temperature and humidity, direction, rainwater sensors sensitive to different soil conditions and measures the actual size of the sole. The main purpose of this project is to manage water supply. And installation monitoring via smartphone. This page is about irrigation systems. related to Our project help explains how irrigation can be implemented using IoT.